The VH repertoire and clonal diversification of B cells in inflammatory myopathies. Issue 2 (16th January 2014) - McIntyre, Donna; Zuckerman, Neta S.; Field, Max; Mehr, Ramit; Stott, David I.
<x xml:space="preserve">Abstract</x> The contribution of antigen‐driven B‐cell adaptive immune responses within the inflamed muscle of inflammatory myopathies (IMs) is largely unknown. In this study, we investigated the immunoglobulin VH gene repertoire, somatic hypermutation, clonal diversification, and selection of infiltrating B cells in muscle biopsies from IM patients (dermatomyositis and polymyositis), to determine whether B cells and/or plasma cells contribute to the associated pathologies of these diseases. The data reveal that Ig VH gene repertoires of muscle‐infiltrating B cells deviate from the normal VH gene repertoire in individual patients, and differ between different types of IMs. Analysis of somatic mutations revealed clonal diversification of muscle‐infiltrating B cells and evidence for a chronic B‐cell response within the inflamed muscle. We conclude that muscle‐infiltrating B cells undergo selection, somatic hypermutation and clonal diversification in situ during antigen‐driven immune responses in patients with IMs, providing insight into the contribution of B cells to the pathological mechanisms of these disorders.